ChemInform Abstract: A Highly Enantioselective Acyl‐Mannich Reaction of Isoquinolines with Aldehydes Promoted by Proline Derivatives: An Approach to 13‐Alkyl‐tetrahydroprotoberberine Alkaloids. Issue 9 (March 2015) - Mengozzi, L.; Gualandi, A.; Cozzi, P. G.
Abstract The new method affords alkylated isoquinolines as diastereomeric mixtures with high enantioselectivities.